Thailand - Levine, Charles; Hoefer, Hans; Warren, William; Black, Star; Burrows, Robert; Dillon, Jerry; Grace, Nancy; Green, Frank; Stirling, John; Wheeler, Tony; Brooke, Marcus (Apa Productions Hong Kong, 1980)
Travel guide to Thailand.
Includes Bibliography and Index
Keywords: Description and travel -- Thailand; Guidebooks. -- Thailand